The big trail - Wayne, John.; Power, Tyrone ([United States] : 20th Century Fox, 2008)
In this sweeping pioneer adventure, a courageous young scout leads hundreds of settlers across treacherous cliffs, though brutal snowstorms, Indian attacks, and buffalo stampedes to their destiny out West. This film made John Wayne a star.
Features both the70 mm widescreen and the alternative standard fullscreen version, plus three featurettes.
Director, Raoul Walsh.
Tyrone Power, John Wayne.
Rated NR.
DVD.
Keywords: Western films; Feature films